New Constraints on Assemblage‐Driven Variation in the Relationship Amongst Diatom‐Bound, Biomass, and Nitrate Nitrogen Isotope Values. Issue 8 (4th August 2022) - Jones, C. A.; Closset, I.; Riesselman, C. R.; Kelly, R. P.; Brzezinski, M. A.; Robinson, R. S.
Abstract: Tracking variations in the surface ocean supply and demand of nitrate, a key marine nutrient, can help constrain the contribution of biological production in driving past climate shifts. The nitrogen isotopic composition (as δ 15 N) of organic matter in marine sediments is a proxy for surface ocean nitrate supply and demand over time, but it may be subject to alteration during sinking and burial. The isotopic composition of nitrogen occluded in the opal shells, or frustules, of diatoms (δ 15 NDB ) is protected and is, therefore, a potentially more robust tracer of nitrate use in the past. Here, we show that δ 15 NDB in Southern Ocean growout cultures of natural communities does not depend on species composition. We found that the εDB (= biomass δ 15 N–δ 15 NDB ) of the community growouts was −4.8 ± 0.8‰, more than 10‰ different from previous monospecific growouts, but statistically indistinguishable from previous Southern Ocean and North Pacific surface ocean observations. The two community growouts, seeded with populations from ∼66° to ∼61°S, had distinct community compositions, but indistinguishable εDB, suggesting that species composition does not primarily set δ 15 NDB values, at least in Antarctic and Polar Frontal Zones of the Southern Ocean. Our results demonstrate that under nitrate‐replete conditions, δ 15 NDB values of frustules sinking from the surface ocean robustly track surface ocean nitrate δ 15 N values, and therefore nitrate supply and demand. Key Points: In natural community growouts, δ 15 NDB values are higher than δ 15 Nbiomass values—opposite of prior monospecific diatom growouts The relationship between δ 15 Nbiomass and δ 15 NDB was the same in community growouts and in surface ocean particles Two distinct, diatom‐dominated Southern Ocean communities produced indistinguishable δ 15 NDB values, when grown on the same nitrate pool